The Ngorongoro Crater as the biggest geotouristic attraction of the Gregory Rift (Northern Tanzania, Africa) – geotouristic valorization, touristic development and hazard - Żaba, Jerzy; Gaidzik, Krzysztof (Geotourism/Geoturystyka, 2025)
The Ngorongoro Crater, as the largest unflooded and not destroyed volcanic caldera on Earth, is one of the major geotouristic attractions of East Africa. Unique on the global scale richness of wildlife, exotic cultures of indigenous people and specific position of the Crater within the East African Rift System, each year attracts thousands of tourists eager for an unforgetable experience. Their number continues to grow from year to year, reaching the value of nearly half a million visitors within the last few years. Constantly developing tourism industry, besides many advantages, also causes a number of risks, both for the world of living nature and inanimate nature objects, as well as for the local population. In 1959, recognizing the unique and special touristic and geoeducative values of this location, the Ngorongoro Conservation Area (NCA) was established. Almost twenty years later, in 1978, the area was included in the UNESCO World Cultural and Natural Heritage List. Furthermore, within the Ngorongoro Conservation Area as well as in its immediate neighborhood there are many objects that also deserve to be called geotouristic attractions, such as: Olduvai Gorge, Crater Olmoti, Crater Empakai and Oldoinyo Lengai volcano. In a relatively short distance from the Crater also the highest mountain in Africa – the Kilimanjaro volcano and the biggest active volcano of this continent, Meru, are located.